ANALISIS KETERAMPILAN BERBICARA MELALUI METODE DISKUSI KELOMPOK PADA SISWA KELAS 3C SDN SENDANGMULYO 02 SEMARANG - Nur Fadhilah; Ervina Eka Subekti; Dina Prasetyowati; Rafika Nuriafuri (STKIP Subang, 2023)
This study aims to describe speaking skills through group discussions of class III students at SD Negeri Sendangmulyo 02 Semarang and describe the factors that influence the speaking skills of class IIIC students at SDN Sendangmulyo 02 Semarang for the academic year 2022/2023. This type of research is descriptive qualitative. This research was conducted in class IIIC at SDN Sendnagmulyo 02 Semarang, Tembalang District, Semarang City for the 2022/2023 school year because the consideration that the school had problems related to the speaking skills of class IIIC students and the teacher's lack of attention to speaking skills. Data analysis is carried out after collecting data according to the objectives to be achieved. This data collection uses an interview guideline instrument and an observation sheet in the form of an assessment rubric. In this study, researchers used a qualitative descriptive analysis technique. The results showed that the results of observing speaking skills through the group discussion method of class IIIC students at SD Negeri Sendnagmulyo 02 Semarang were successful. A description of the factors that influence speaking skills through the group discussion method of class IIIC students at SD Negeri Sendangmulyo 02 Semarang, namely internal factors and external factors. Internal factors include the intensity of the use of the local language, family factors, and individual or student factors. External factors include environmental factors, teacher factors, and the availability of facilities and infrastructure.